Spiritual Care in the Intensive Care Unit: A Narrative Review. (May 2018) - Ho, Jim Q.; Nguyen, Christopher D.; Lopes, Richard; Ezeji-Okoye, Stephen C.; Kuschner, Ware G.
Spiritual care is an important component of high-quality health care, especially for critically ill patients and their families. Despite evidence of benefits from spiritual care, physicians and other health-care providers commonly fail to assess and address their patients' spiritual care needs in the intensive care unit (ICU). In addition, it is common that spiritual care resources that can improve both patient outcomes and family member experiences are underutilized. In this review, we provide an overview of spiritual care and its role in the ICU. We review evidence demonstrating the benefits of, and persistent unmet needs for, spiritual care services, as well as the current state of spiritual care delivery in the ICU setting. Furthermore, we outline tools and strategies intensivists and other critical care medicine health-care professionals can employ to support the spiritual well-being of patients and families, with a special focus on chaplaincy services.